Pengaruh Motivasi dan Kompetensi Guru terhadap Hasil Belajar Siswa pada SD Negeri di Kecamatan Sematang Borang Palembang - Mita Anggraini; Syarwani Ahmad; Mahasir Mahasir (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to determine and describe the influence of teacher motivation and competence on student learning outcomes at public elementary schools in the District of Sematang Borang Palembang. This research was conducted at a public elementary school in the District of Sematang Borang Palembang. The type of research used in this seresearch is quantitative research. The total population in this study was 100 teachers. Data collection techniques in this study were carried out in several ways, namely questionnaires, interviews and documentation. The data analysis technique used is a multiple regression model with the help of SPSS for Windows. The results of the study concluded that partially Motivation had a positive and significant effect on Student Learning Outcomes at Public Elementary Schools in Sematang Borang District, Palembang City and Teacher Competence had a positive and significant effect on Student Learning Outcomes at Public Elementary Schools in Sematang Borang District, Palembang City. Meanwhile, simultaneously Teacher Motivation and Competence have a significant effect on Student Learning Outcomes at Public Elementary Schools in Sematang Borang District, Palembang. In conclusion, teacher motivation and competence influence elementary school student learning outcomes. Keywords: Motivation, Teacher Competence, Learning Outcomes